Social class, parenting, and child development: A multidimensional approach. (February 2022) - Cano, Tomás
Abstract: Children from upper-class families have better cognitive outcomes and fewer behavioural problems than those from working-class families. Previous studies highlighted that the class gap in child development is partially driven by differences in parenting styles, but they rarely looked at multiple, more specific dimensions of parenting, i.e., inductive reasoning, parenting consistency, warmth and anger. This study provides a systematic account of how parental social class shapes these four dimensions of parenting, and how these dimensions affect children's cognitive outcomes and behavioural problems. Using high-quality, longitudinal data, and both hybrid models and the generalized methods of moments, this study reports two main findings. First, upper-class parents significantly differ from lower-class parents in two parenting dimensions, displaying more inductive reasoning and parenting consistency, but no relevant class differences are found in the two emotion-type dimensions of parenting (i.e., warmth and anger ). Second, all four parenting dimensions have a strong impact on children's behavioural problems, while they do not affect cognitive outcomes. An exception is consistency, the only dimension that affects both types of child outcomes. The study underscores the relevance of analysing parenting and child development from a multidimensional approach to better understand how upper-class parents transmit advantage to children.